(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The objective of the present study is to describe the implementation of a token economy system in an institution, demonstrating how this system can be useful to Applied Behavior Analysis. The implementation resulted from a demand of the institution administration to solve a problem related to the performance of the employees regarding hygiene behaviors and the presentation of these behaviors. The implementation was conducted after the identification of the institution problems. This identification was made through observation of the institution’s working methods and was influenced by Behavior Analysis notions. The present description presents all the stages of the process, from the choice rationale to the intervention evaluation. To evaluate the effectiveness of the intervention to overcome the institution problems, an ABAB design was used and 104 employees of the institution participated.